2019
DOI: 10.1002/joc.6168
|View full text |Cite
|
Sign up to set email alerts
|

Impact of differences in the decaying phase of El Niño on South and East Asia summer monsoon in CMIP5 models

Abstract: The present study examined the ability of Coupled Model Intercomparison Project phase 5 (CMIP5) models in representing the differences in decaying phases of El Niño and their impact on south Asia and east Asia monsoon during June and July (JJ), the early summer monsoon months. El Niño decay is classified into three categories, based on the timing of decay with respect to the summer season after the peak phase of El Niño. Analysis suggests that many CMIP5 models are able to capture the differences in the decayi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 72 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…For example, the relationship between ENSO and precipitation over northeastern China (western Russia surface temperature) after the mid-1990s (1980s) was strengthened during summer, which means that changes in climate elements in one place are not always affected by the same climate phenomena. Furthermore, some studies have also shown the significant impact of the decaying phase of El Niño on the Asian summer monsoon using CMIP5, indicating that numerical modeling is a valuable way to explore the instability [28]. For these reasons, studying the unstable relationship between two weather systems will provide new ideas for understanding the physical mechanisms existing under the different climate conditions in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the relationship between ENSO and precipitation over northeastern China (western Russia surface temperature) after the mid-1990s (1980s) was strengthened during summer, which means that changes in climate elements in one place are not always affected by the same climate phenomena. Furthermore, some studies have also shown the significant impact of the decaying phase of El Niño on the Asian summer monsoon using CMIP5, indicating that numerical modeling is a valuable way to explore the instability [28]. For these reasons, studying the unstable relationship between two weather systems will provide new ideas for understanding the physical mechanisms existing under the different climate conditions in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The difference of atmospheric environment between ST and RT El Niño events not only exists in the tropical region, but also in the subtropical and mid‐latitude. One of the obvious characteristics is the enhanced anticyclone anomalies over the WNP subtropical region during the RT El Niño events (Srinivas et al, 2019; Zhou et al, 2019). The anomalous anticyclone is weak in ST events (Figure 6a), while it is strengthened in RT El Niño events due to the colder SST anomalies in the tropical central‐eastern Pacific (Figure 6b).…”
Section: Possible Mechanismsmentioning
confidence: 99%